2018
DOI: 10.1186/s12933-018-0762-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between insulin resistance and the development of cardiovascular disease

Abstract: For many years, cardiovascular disease (CVD) has been the leading cause of death around the world. Often associated with CVD are comorbidities such as obesity, abnormal lipid profiles and insulin resistance. Insulin is a key hormone that functions as a regulator of cellular metabolism in many tissues in the human body. Insulin resistance is defined as a decrease in tissue response to insulin stimulation thus insulin resistance is characterized by defects in uptake and oxidation of glucose, a decrease in glycog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
1,057
4
49

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,431 publications
(1,137 citation statements)
references
References 180 publications
(203 reference statements)
27
1,057
4
49
Order By: Relevance
“…Insulin resistance caused by weight gain and visceral fat accumulation may lead to hyperinsulinaemia, which might prompt not only further weight gain but also cardiometabolic disorders associated with the risk of cardiovascular disease . A decline in hepatic insulin clearance is one of the causes of hyperinsulinaemia .…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance caused by weight gain and visceral fat accumulation may lead to hyperinsulinaemia, which might prompt not only further weight gain but also cardiometabolic disorders associated with the risk of cardiovascular disease . A decline in hepatic insulin clearance is one of the causes of hyperinsulinaemia .…”
Section: Discussionmentioning
confidence: 99%
“…IR can also alter systemic lipid metabolism, leading to the generation of dyslipidemia. Along with endothelial dysfunction, which can also be created by an abnormality of insulin signaling, IR contributes to the atherosclerotic plaque production [36].…”
Section: Discussionmentioning
confidence: 99%
“…IR in the myocardium produces damage by signal transduction modification, impaired regulation of substrate metabolism, and variation in the delivery of substrates to the myocardium [36].…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) manifests characteristics of insulin resistance and hyperinsulinemia, and hence insulin therapy that often associates with cardiovascular damage and coronary artery calcification poses several adverse effects (Ormazabal et al, 2018). As an alternative, randomized clinical studies on dietary carbohydrate constraint or KD showed an improved glucose metabolism and glycemic control, reducing the use of antiglycemic medication (Westman, Tondt, Maguire, & Yancy, 2018).…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%